2009
DOI: 10.1002/lt.21735
|View full text |Cite
|
Sign up to set email alerts
|

The model for end-stage liver disease score is the best prognostic factor in human immunodeficiency virus 1-infected patients with end-stage liver disease: A prospective cohort study

Abstract: End-stage liver disease (ESLD) has become the main cause of mortality in patients coinfected by human immunodeficiency virus (HIV) and hepatitis B virus or hepatitis C virus in developed countries. The aim of this study was to describe the natural history of and prognostic factors for ESLD, with particular attention paid to features affecting liver transplantation. This was a prospective cohort study in 2 Spanish community-based hospitals performed between 1999 and 2004. One hundred four consecutive patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 23 publications
1
41
0
3
Order By: Relevance
“…In fact, the predictive value of MELD score in HIV/HCV-coinfected patients remains controversial, with previous studies reporting no independent association with survival 6,33 and others finding such an association. 34,35 In our opinion, the lack of an independent association of MELD with liver-related mortality in our cohort could reflect a weaker predictive value in the long term, as is the case in this study, than in the short-and mid-term. Achievement of SVR after treatment of hepatitis C is associated with a reduction in liver-related mortality in HIV-negative 36 and HIV-positive patients.…”
Section: Discussionmentioning
confidence: 51%
“…In fact, the predictive value of MELD score in HIV/HCV-coinfected patients remains controversial, with previous studies reporting no independent association with survival 6,33 and others finding such an association. 34,35 In our opinion, the lack of an independent association of MELD with liver-related mortality in our cohort could reflect a weaker predictive value in the long term, as is the case in this study, than in the short-and mid-term. Achievement of SVR after treatment of hepatitis C is associated with a reduction in liver-related mortality in HIV-negative 36 and HIV-positive patients.…”
Section: Discussionmentioning
confidence: 51%
“…These include [20], ascites (abdominal distention, shifting dullness, and confirmed fluid by paracentesis or abdominal imaging), variceal bleeding (endoscopic evaluation with upper gastrointestinal hemorrhage, 35-85% with cirrhosis; bleeding 25-40%; 30-50% 3 month survival), spontaneous bacterial peritonitis (>500 white blood cells/mL, >250 polymorphonuclear cells/mL, positive culture), hepatic hydrothorax (right sided pleural effusion), and hepatic encephalopathy (asterixis flapping tremor). Management requires aggressive diuresis, pleural taps, and immediate consideration for liver transplantation based on the MELD (Model for End Stage Liver Disease) [21].…”
Section: Discussionmentioning
confidence: 99%
“…The inability to achieve an undetectable plasma HIV RNA viral load before LT is associated with an increased risk of death [hazard ratio (HR) ¼ 3.47, 95% confidence interval (CI) ¼ 1.94-6.17, P < 0.001]. 46 It is important that patients undergoing an assessment for LT have adequate future cART treatment options that are based on their previous treatment history and HIV genotype resistance testing. Because of the hepatotoxicity associated with cART in patients with ESLD, some patients may not be able to tolerate antiretroviral therapy before LT.…”
Section: Selection and Listing Criteria For Lt In Hiv-positive Indivimentioning
confidence: 99%
“…Two more recent prospective studies 46,50 have suggested that the MELD score may be an important The criteria for LT are met. The CD4 þ cell count is >100 cells/lL (>200/lL if there is a history of opportunistic complications).…”
Section: Selection and Listing Criteria For Lt In Hiv-positive Indivimentioning
confidence: 99%
See 1 more Smart Citation